High visceral adiposity index is associated with female orgasmic disorder in premenopausal women: a cross-sectional study. (18th August 2022) - Sahin, Yusuf; Karacan, Tolga; Hacibey, Ibrahim; Aybek, Ozlem Yuksel; Ozer, Zeynep; Cil, Gokhan; Dincer, Muhammet Murat; Guraslan, Hakan; Muslumanoglu, Ahmet Yaser
Abstract: This study aimed to evaluate the association between the visceral adiposity index (VAI) and female sexual dysfunction (FSD). This cross-sectional study included 165 premenopausal, sexually active women admitted to the gynaecology outpatient clinic between January 2021 and April 2021. Female Sexual Function Index (FSFI) was used to assess the sexual function of the women. After measuring body mass index (BMI) and waist circumference (WC), biochemical serum analysis was performed. The VAI was calculated for all participants. The relationship between VAI and total FSFI and subdomain scores was investigated. Of the participants, FSD was detected in 65.5%. There was no relationship between the total FSFI scores and age, BMI, WC and VAI ( p  = .126, p  = .675, p  = .790, p  = .220, respectively). Increased VAI levels were associated with dysfunction in orgasm ( p  = .008). Although VAI seems not to be directly related to FSD, it may predict the orgasmic disorder in women. Impact Statement: What is already known on this subject? Obesity and female sexual dysfunction (FSD) are common health problems which adversely affect the biopsychosocial well-being. Although the relationship between FSD and obesity, body mass index (BMI) and waist circumference (WC) has been widely discussed in the literature to date, there is not enough evidence for the link between FSD and visceral adiposity index (VAI) which is a reliable indicator of visceral fat dysfunction. What do the results of this study add? The results of this study showed that none of the factors indicating obesity such as BMI, WC and VAI were correlated with the total FSFI scores. However, a significant positive correlation was found between the VAI and female orgasmic disorder (FOD). What are the implications of these findings for clinical practice and/or further research? The VAI may be a useful tool for detecting FOD patients. Diagnosis and treatment of orgasmic disorder would significantly improve the patient's quality of life and general well-being. Further large-scale and high-evidence studies are needed to clarify the impact of obesity on FSD and the relationship between VAI and FOD.